Tune‐out and magic wavelengths for hydrogenlike and screened‐hydrogenlike atoms. Issue 5 (23rd November 2019) - Wang, Yu‐Shu; Kar, Sabyasachi; Ho, Yew Kam
Abstract: The tune‐out and magic wavelengths (TMWs) for the hydrogenlike and screened‐hydrogenlike atoms ( Z = 1‐8) are calculated using a variational method. The first three tune‐out wavelengths for each of the n S (n = 1, 2, 3) states and the first three magic wavelengths for each of the 1 S ‐n S (n = 2, 3) transitions of the hydrogenlike atoms in terms of nuclear charge Z, and the first TMWs for the above mentioned states or transitions of the screened‐hydrogenlike atoms in terms of the screening parameter μ and Z are presented. All the results for the TMWs are reported for the first time in the literature except the magic wavelengths for the hydrogen atom. The magic wavelengths for hydrogen atom are in agreement with the available data. The precise estimation of the TMWs would be helpful for the design of the ion‐trapping experiment of the hydrogenic systems. Our study is expected to be useful for the measurements of the hydrogenic 1 S ‐2 S and 1 S ‐3 S transitions spectroscopy for the improved accuracy. Abstract : The magic wavelength is the special wavelength at which the ac Stark shifts for a particular state and an upper excited state of an atomic species are equal. The tune‐out wavelength is instead based on the strength of induced dipole moment by tuning the laser wavelength close to the atomic resonance. Both wavelengths are reported for various states in terms of nuclear charge for hydrogenlike atoms, and terms of the screening parameter for screened‐hydrogenlike atoms.